ANALISIS KARAKTERISTIK SPBU DI KAWASAN CEPAT BERKEMBANG KOTA SEMARANG BAGIAN SELATAN - Awan Ariseto Moelyanto; Imam Buchori (Teknik PWK (Perencanaan Wilayah Kota), 2012)
At recent days, the growth of motor vehicle is equal to the growth of public activities and the growth of area. It increases the needs of fuel, so that it increasing number of gas station in Semarang to the remote area. Remote area of Semarang, especially in Tembalang subdistrict and Banyumanik subdistrict, has been developed significantly because there are some interests such as comfortable settlement, ideal business area, crowded activities area (education centre, settlement, trading area and service system area) and existense of space.The growth of Tembalang subdistrict and Banyumanik subdistrict is followed by the growth of supporting public facilities such as stores, hospital, post office, gas station, etc. The purpose of this research is to identify characteristic and knowing the range area for spreading gas station services toward the consumer in research area. This research is done through character knowledge of gas station location in arterial setyabudi street in Banyumanik subdistrict and tembalang street in Tembalang subdistrict and latter by knowing the consumer spreading of its gas station.This research applied quantitative approach and collecting primary data method through the interview,in field observation, spreading questionaires and collecting secondary data from instantion. The result of this research is comaparative character of each gas station location along arterial Setiabudi street in Banyumanik subdistrict and tembalang street in Tembalang subdsitrict. The result of this research is highly hoped to given some consideration in evaluating the gas station location through effectivity and improper of gas station location toward consumer’s need, so that there will be optimalization of those ga stations or the gas station new set.